Protein disulfide isomerases regulate androgen receptor stability and promote prostate cancer cell growth and survival - Jianling Xie; Kaikai Shen; Wenken Liang; Zijian Kuang; Raj K. Shrestha; Adrienne R. Hanson; Scott L. Townley; Meiling He; Sishu Yu; Peiwen Zhou; Liangzhen Zhu; Zhiwen Gong; et al. (Proceedings of the National Academy of Sciences, 2025)
Cancer cells exhibit accelerated protein production to accommodate their high rates of growth and proliferation. Elevated protein synthesis creates a dependency on endoplasmic reticulum (ER)-resident proteins and chaperones, which are required to maintain proteostasis. In this study, we identified the protein disulfide isomerases (PDIs) PDIA1 and PDIA5, which play a critical role in folding of client proteins in the ER, as important regulators of prostate cancer growth and response to therapy. PDIA1 and PDIA5 are upregulated in prostate cancer and induced by the androgen receptor (AR) signaling axis. Genetic or pharmacological disabling of PDIA1/PDIA5 caused redox stress, mitochondrial dysfunction, growth inhibition, and death of prostate cancer cells in vitro and in vivo. The critical functions of these enzymes in redox homeostasis and cell survival were observed in both AR-driven and AR-independent models of prostate cancer. Loss of PDIA1/PDIA5 activity led to ubiquitination and degradation of the AR, revealing a feedback loop between these chaperones and the AR pathway. Mechanistically, PDIA1/PDIA5 regulated AR stability by mediating disulfide bond formation, an activity that required cysteines 669 and 844 in AR’s ligand-binding domain. Importantly, targeting PDIAs sensitized prostate cancer cells to the AR antagonist, enzalutamide. This study reveals a mechanism governing AR proteostasis in prostate cancer and positions PDIA1/5 as viable therapeutic targets.